Three-dimensional pelvic kinematics in healthy, total hip arthroplasty, and lumbar fusion patients using stereo-radiography - Colone, Kathryn H.; Quinlan, Nicole D.; Mattei, Sam R.; Shelburne, Kevin B.; Rullkoetter, Paul J.; Dennis, Douglas A.; Clary, Chadd W.; Myers, Casey A. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMeasuring pelvic tilt and pelvic obliquity during functional positions is important for surgical planning of total hip arthroplasty as these orientations affect optimal acetabular cup position and post-operative hip stability. The objective of this study was to compare pelvic tilt, pelvic obliquity, and pelvic mobility across 3 cohorts of age-matched patients: 1) healthy controls 2) THA patients without spinal fusion and 3) patients with instrumented spinal fusions. We hypothesized that (1) the healthy and THA cohorts would demonstrate similar pelvic mobility across the range of position demand and (2) individuals with spinal fusions would have significantly less pelvic mobility than both the healthy and THA cohorts.MethodsWe compared 10 patients in each of these cohorts using stereo radiography to quantify pelvic tilt and pelvic obliquity across a range of clinically relevant poses of varying demand on pelvic mobility.ResultsResults demonstrated that the overall pelvic mobility of the spinal fusion cohort was consistently similar in magnitude to health controls but biased anteriorly by 6.5% and 33.5% compared to the healthy and total hip cohorts, primarily due to less posterior tilting across the functional positions (Healthy: 39.6° ± 10.2°; Spinal fusion: 39.5° ± 7.3°; Total hip: 37.8° ± 7.6°). Obliquity angles varied substantially between some clinically relevant pose combinations. Low and high coronal plane mobility patients were identified in each of the three cohorts, with mobility ranging between 4.4° and 28.3°, respectively, across positions.DiscussionSubstantial intragroup variability was exhibited within each cohort across the six functional poses, highlighting the patient-specific nature of the spinopelvic relationship regardless of previous surgery at the hip or spine. The larger pelvic tilt angles demonstrated during more demanding poses in seated and standing highlights the importance of imaging patients in poses that capture the full extent of pelvic mobility.